APAKAH PEMUDA DESA MENGETAHUI OBYEK WISATA DI DESANYA? Gambaran Pengetahuan Pemuda Tentang Potensi Wisata Desa Ciasmara Kecamatan Pamijahan Kabupaten Bogor - Yogaprasta Adi Nugraha; David Rizar Nugroho; Mariana Rista Ananda Siregar; Restu Maharani Dewi (UNIVERSITAS PAKUAN, 2021)
This study was conducted to identify the perception of rural youth on tourism potential in Ciasmara Village. In addition, this study also tries to describe individual characteristics, frequency of visits to tourist objects, analyse the relationship between individual characteristics and frequency of visits with youth perceptions. Indicators on individual characteristics include age, gender, and level of education. Indicators on the frequency of youth visits include the frequency of visits to waterfalls and the frequency of visits to hot springs. The research was carried out in Ciasmara Village, Pamijahan District, Bogor Regency from April 2019 to August 2020. This method uses two approaches, namely a Survey approach to see the distribution of perceptions. The sampling technique used was purposive sampling technique with descriptive-correlational quantitative methods, descriptive statistical data analysis techniques and non-parametric statistics (Rank Spearman Chi-Square). This research found that youth in Ciasmara village have a positive perception of tourism potential in Ciasmara village but from the results of in-depth interviews it was also found that there are several challenges that need to be considered if they want to develop Ciasmara Village as a tourist village